1995
DOI: 10.2176/nmc.35.144
|View full text |Cite
|
Sign up to set email alerts
|

<I>Intraoperative Spinal Sonography in the Cervical Anterior Approach</I>

Abstract: Intraoperative spinal sonography was used during cervical anterior approach procedures for cervical discectomy and osteophytectomy to demonstrate spinal pulsation, the protruded disc or osteophyte, the anterior subarachnoid space, and the spinal cord. Spinal pulsation was recognized in some cases before removal of the disc but the anterior subarachnoid space and spinal cord could not be observed. However, the latter were more clearly observed during removal of the disc and could be seen after total removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Imamura et al [17] reported the use of US during spinal decompression surgery to generate images of deep-lying structures during anterior cervical surgical approach. These structures are difficult to visualize without US.…”
Section: Intra-operative Usmentioning
confidence: 99%
“…Imamura et al [17] reported the use of US during spinal decompression surgery to generate images of deep-lying structures during anterior cervical surgical approach. These structures are difficult to visualize without US.…”
Section: Intra-operative Usmentioning
confidence: 99%